Homoconjugation effects in triptycene based organic optoelectronic materials. Issue 3 (17th January 2023) - Mistry, Jai-Ram; Montanaro, Stephanie; Wright, Iain A.
Abstract : Homoconjugation occurs when two aromatic rings are separated by a single non-conjugated atom. This is demonstrated in triptycene by the through-space overlap of the π-clouds of the aryl fins and can be used to enhance optoelectronic properties. Abstract : Molecular size and shape have a commanding influence on the electronic structure and photophysical properties of organic optoelectronic molecules. Small changes in, for example, the dihedral angles between two rings in a molecule can be used to fine tune frontier orbital distributions, and make the difference between efficient or poor absorbance, luminescence, charge transport etc. as well as impacting on mechanical and thermal properties to improve processability. Recent works have made it clear that structural changes which enforce homoconjugation, the through-space overlap of frontier π-orbitals across a shared non-conjugating group, can exert even more dramatic changes on these useful functional properties. Triptycene is an archetypical homoconjugated molecule with a rigid 3D structure which presents an ideal substrate from which to learn how best to employ homoconjugation to optimise functional molecular properties. This review demonstrates this by highlighting triptycene-based molecules in the context of organic electronic materials, where homoconjugation has resulted in markedly enhanced optoelectronic properties, and provides comment on the performance and future potential of these materials in devices where possible.